Study the Correlation between Serum level of Interlukin 6 and Lactate Dehydrogenase in Myeloma Patients at Stage III with Serum Creatinine and Calcium Level (Medico Legal Update, 2020)
Multiple myeloma (MM) still an incurable disease that require better recognition and more research. Manyprevious studies shown the interaction between myeloma cells and bone marrow stromal cells for the initiationand progression of multiple myeloma . Many chemokines and their receptors including interleukin-6 (IL-6)an play important roles in this interaction. The main purpose of this study is assess the serum level of IL-6and Lactate dehydrogenase on stage-III of MM patients and healthy controls then Finding the correlationwith creatinine and calcium levels. Serum level of IL-6 , Lactate Dehydrogenase , creatinine and calciumlevels of (30) MM patients diagnosis at stage –III according to International staging System (ISS) weremeasurement. The results for these parameters compare with (30) age- and sex-matched healthy controlsgroups. The results were showed that the mean levels of IL-6 , Lactate dehydrogenase , creatinine andcalcium (increased or decreased)high significant (p?0.001) when compared with healthy controls . Theresults of the study suggested the important role of chemokines including IL-6 in the progression of thedisease and its relationship with some biochemical parameters , especially in the stage-III of the disease.